South-South Trade Growth Prospects and Policy Implications - Buranawijarn, Panit (Thammasat Review of Economic and Social Policy, 2016)
South-South Trade, or more broadly South-South Cooperation, is the collaboration between developing countries of the Global South across various dimensions such as political, economic, and social issues. This paper analyses trends and developments in the trade between developing countries in contrast to other orientations of trade, focusing particularly on China and India. The paper looks at their trade flows, as well as their other activities which fall under the aegis of South-South Cooperation. Lastly, the literature on South-South Trade is reviewed to study the motivation for engaging and encouraging South-South Trade, as well as its overall effectiveness. Policy recommendations for the development of South-South Trade are made based on evidence from the study.